Interaction of Methods of Calligraphic Writing Teaching in the Process of the Prospective Teacher's Practical Training for Work with First-Formers - Halyna Tkachuk; Halyna Dorosh (Pedagogical Discourse, 2013)
Practical training of the students institutions of higher education for teaching first-formers writing is considered in the article, particularly the optimal combination of such well known methods as: copying, lineal, rhythm, genetic, analitic-synthetic, because such usage of methods allows future teachers to master their style to prepare practically to the work on making primary pupils’ handwriting calligraphic and quick; also the visual aids on calligraphy for students of pedagogical higher educational establishments are analyzed.